Life Threatening Idiopathic Recurrent Angioedema Responding to Cannabis - Amit Frenkel; Aviel Roy-Shapira; Brotfain Evgeni; Koyfman Leonid; Abraham Borer; Moti Klein (Case Reports in Immunology)
We present a case of a 27-year-old man with recurrent episodes of angioedema since he was 19, who responded well to treatment with medical grade cannabis. Initially, he responded to steroids and antihistamines, but several attempts to withdraw treatment resulted in recurrence. In the last few months before prescribing cannabis, the frequency and severity of the attacks worsened and included several presyncope events, associated with scrotal and neck swelling. No predisposing factors were identified, and extensive workup was negative. The patient reported that he was periodically using cannabis socially and that during these periods he was free of attacks. Recent data suggest that cannabis derivatives are involved in the control of mast cell activation. Consequently, we decided to try a course of inhaled cannabis as modulators of immune cell functions. The use of inhaled cannabis resulted in a complete response, and he has been free of symptoms for 2 years. An attempt to withhold the inhaled cannabis led to a recurrent attack within a week, and resuming cannabis maintained the remission, suggesting a cause and effect relationship.